Current therapy guidelines for Waldenstrom's macroglobulinaemia - Kastritis, E.; Dimopoulos, M.A. (Best Practice and Research: Clinical Haematology, 2016)
Waldenstrom's macroglobulinaemia (WM) is a B-cell neoplasm in which bone marrow is infiltrated by lymphoplasmacytic cells that secrete monoclonal immunoglobulin M (IgM). More than a decade ago, specific criteria were agreed to define diagnosis and symptomatic disease requiring therapy; however, treatment recommendations change as new options emerge. Treatment decisions consider specific disease characteristics (burden of disease, IgM levels, presence of cytopenias) and patient characteristics (age, comorbidities, toxicity). Recently, the impact of specific mutations (in MYD88 and CXCR4) in response to specific therapies has been reported, and this may affect treatment decisions in the future. Chemo-immunotherapy combinations based on rituximab with cyclophosphamide/dexamethasone, bendamustine or bortezomib/dexamethasone are indicated for most patients. The BTK inhibitor ibrutinib was recently approved for patients with WM, and is a new option for selected newly diagnosed or relapsing patients. New B-cell receptor inhibitors, second-generation proteasome inhibitors and mammalian target of rapamycin inhibitors are promising; however, more data are needed from high-quality clinical trials. © 2016 Elsevier Ltd
Keywords: bortezomib; Carfilzomib; Fludarabine; ibrutinib; rituximab